Modeling of long‐term screening for lung carcinoma - Gorlova, Olga Y.; Kimmel, Marek; Henschke, Claudia (Cancer, 2001)
BACKGROUND Results from the Mayo Lung Project (MLP), a randomized clinical trial for the early detection of lung carcinoma, were interpreted as proof that the early detection of lung carcinoma by chest X‐ray does not reduce the mortality from this disease. Recent analysis of extended follow‐up data from the MLP subjects found that after approximately 20 years there still was no apparent difference in lung carcinoma mortality between a study group and a control group. METHODS To view this result within context, the authors utilized a previously published simulation model of the MLP, with parametric values that were estimated at the time of the original publication based on the data collected by the MLP. RESULTS The model produced predictions of the extended follow‐up statistics that were found to be consistent with the data published in the prior study. The authors believe this provides long‐term validation for the model. Conversely, the same model demonstrated that had the study subjects been screened annually for the extended follow‐up period, the difference in mortality would be noticeable, even with the low sensitivity of chest X‐ray detection. CONCLUSIONS The results of current study strongly suggest that long‐term screening with chest X‐ray results in a reduction in lung carcinoma mortality. The limited extent of this benefit is the result of the low sensitivity of chest X‐ray as a screening tool. Cancer 2001;92:1531–40. © 2001 American Cancer Society. The results of the current study strongly suggest that long‐term screening with chest X‐ray results in a reduction in mortality from lung carcinoma. The limited extent of this benefit is the result of the poor performance of chest X‐ray as a screening tool.